Kekayaan Jenis Anggrek Di Hutan Alam Desa Beginjan Kecamatan Tayan Hilir Kabupaten Sanggau - Riza Linda, Rizka Amalia, Irwan Lovadi (Jurnal Protobiont, 2015)
The orchid species richness in anecosystem needs to be revealed in order to support the efforts of the biodiversity conservation. This research aims to determine the types of orchids found in the Natural Forest area in the Village of Beginjan, Sub-district of Tayan Hilir, Sanggau Regency. The research was conducted from April 2014 to July 2014 at the Natural Forest of the Village of Beginjan, Sub-district of Tayan Hilir, Sanggau Regency. The samples were taken through the cruise method by exploring the Forest and collecting each sample found. The research found ten different types of natural orchids consisting of seven species of epiphytic orchids, two types of terrestrial orchids and one type of lithophytic orchid. The orchid genus commonly found in this forest is the Bulbophyllum.